Gangliosides Have a Functional Role during Rotavirus Cell Entry - Miguel Ángel Martínez; Susana López; Carlos F. Arias; Pavel Iša (2012)
Cell entry of rotaviruses is a complex process, which involves sequential interactions with several cell surface molecules. Among the molecules implicated are gangliosides, glycosphingolipids with one or more sialic acid (SA) residues. The role of gangliosides in rotavirus cell entry was studied by silencing the expression of two key enzymes involved in their biosynthesis--the UDP-glucose:ceramide glucosyltransferase (UGCG), which transfers a glucose molecule to ceramide to produce glucosylceramide GlcCer, and the lactosyl ceramide-α-2,3-sialyl transferase 5 (GM3-s), which adds the first SA to lactoceramide-producing ganglioside GM3. Silencing the expression of both enzymes resulted in decreased ganglioside levels (as judged by GM1a detection). Four rotavirus strains tested (human Wa, simian RRV, porcine TFR-41, and bovine UK) showed a decreased infectivity in cells with impaired ganglioside synthesis; however, their replication after bypassing the entry step was not affected, confirming the importance of gangliosides for cell entry of the viruses. Interestingly, viral binding to the cell surface was not affected in cells with inhibited ganglioside synthesis, but the infectivity of all strains tested was inhibited by preincubation of gangliosides with virus prior to infection. These data suggest that rotaviruses can attach to cell surface in the absence of gangliosides but require them for productive cell entry, confirming their functional role during rotavirus cell entry.